1991
DOI: 10.1159/000116673
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Hemodynamics in Low-Birth-Weight Infants Treated with Phototherapy

Abstract: Changes of cerebral blood flow were determined in 20 preterm infants undergoing blue-light phototherapy for hyperbilirubinemia. All were healthy very-low-birth-weight infants (< 1,500 g) with normal brain sonograms and not under pharmacological treatment at the time of the investigation. Blood flow velocity (pulsatility index and area under velocity curve) was measured by Duplex Scan technique during and after phototherapy. No changes of global cerebral blood flow were observed in the anterior cerebral artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Amato et al suggested that blue light phototherapy did not affect cerebral blood flow velocity in healthy lowbirthweight infants (8) and in term infants (24). However, they only measured V mean during and after phototherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amato et al suggested that blue light phototherapy did not affect cerebral blood flow velocity in healthy lowbirthweight infants (8) and in term infants (24). However, they only measured V mean during and after phototherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The course of cerebral blood flow velocity during phototherapy has been previously studied in healthy preterm infants (8). No significant changes were observed.…”
mentioning
confidence: 99%
“…Cerebral haemodynamics during conventional phototherapy (CPT) were first studied by Amato et al (1991a), who did not report significant changes in cerebral blood flow velocity (CBFV) in healthy preterm infants. However, Benders et al (1998b) found a significant increase in CBFV, both in healthy and 'unhealthy' preterm infants undergoing phototherapy.…”
mentioning
confidence: 99%
“…Amato and Donati found no effect of phototherapy on cerebral circulation in either preterm [10] or term [11] infants. However, they measured CBFV during and after phototherapy, but not at baseline.…”
Section: Discussionmentioning
confidence: 93%